El filo diestro del durmiente de Héctor Fernando Vizcarra: intertexto, estructura y mirada escópica - Néstor Ponce (Babel: Littératures Plurielles, 2022)
This article analyses the crime novel El filo diestro del durmiente (2013), by the Mexican Héctor Fernando Vizcarra, on the basis of two thematic axes: the dialectical movement between linguistic registers and structure, on the one hand, and the scopic gaze, on the other. The different discursive strata (thriller, narratology, urban orality, mass media) are traversed by a point of view that looks in depth at the mechanisms of the construction of reality. Vizcarra leaves aside superficial observation and delves into the aesthetics of representation to reflect on modern times.